2016
DOI: 10.1007/s11606-016-3792-1
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity and Adoption of a Population Health Management Approach to Colorectal Cancer Screening in a Community-Based Healthcare System

Abstract: BACKGROUND: Screening outreach programs using population health management principles offer services uniformly to all eligible persons, but racial/ethnic colorectal cancer (CRC) screening patterns in such programs are not well known. OBJECTIVE: To examine the association between race/ ethnicity and the receipt of CRC screening and timely follow-up of positive results before and after implementation of a screening program. DESIGN: Retrospective cohort study of screen-eligible individuals at the Kaiser Permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 44 publications
(44 reference statements)
7
57
0
Order By: Relevance
“…In general, FIT screening was associated with a lower number of procedures subject to coinsurance. If FIT screening becomes more popular in the United States similar to trends observed in several settings (37, 38), the costs of waiving the coinsurance will be even lower.…”
Section: Discussionmentioning
confidence: 90%
“…In general, FIT screening was associated with a lower number of procedures subject to coinsurance. If FIT screening becomes more popular in the United States similar to trends observed in several settings (37, 38), the costs of waiving the coinsurance will be even lower.…”
Section: Discussionmentioning
confidence: 90%
“…When necessary, we contacted study authors to specify screening versus symptomatic patients and the absolute numbers of participants who had colonoscopy. One study was excluded because it included symptomatic patients (28), and another because the intervention was unclear without additional information (29). One author provided additional results not available in the report (30); 4 authors of included studies either did not respond or no longer had access to the study data set (31–35).…”
Section: Methodsmentioning
confidence: 99%
“…Despite rapid CRC screening uptake throughout the program, recent studies of the program reported lower odds of CRC screening in blacks and Hispanics relative to whites, calling for increased understanding of these differences. 16,17 Thus, the objective of the present study was to examine time to receipt of CRC screening from age 50 years in a program with uniform population health approaches to delivery of screening according to race/ethnicity. Detailed patterns of the type of test utilized to better understand potential racial differences in CRC screening within the organized screening program were also examined.…”
Section: Introductionmentioning
confidence: 99%